Diabetes mellitus tipo 2 como factor de riesgo asociado a tuberculosis pulmonar multidrogo resistente (TB-MDR) en pacientes adultos - Chávez Arosemena, Tracy Sharlot (2017)
Objective: To determine whether diabetes mellitus 2 is a risk factor associate for multidrug-resistant pulmonary tuberculosis in adult patients. Materials and methods: We performed an observational and analytical case-control study. The group of cases was represented by 73 patients diagnosed with Multidrug-resistant pulmonary tuberculosis and the control group by 219 patients with a diagnosis of sensitive pulmonary tuberculosis. Both groups were evaluated at Regional teaching Hospital of Trujillo, during the period January 2004 to December 2014. The Information was obtained from the medical record in the data collection file. Descriptive and analytical statistics were used to process the data. The Odds ratio calculation determined the association of Diabetes mellitus 2 and multidrug-resistant pulmonary tuberculosis, p <0.05. Results and conclusions: The data obtained were processed in Excel program and analyzed with the statistical package IBM SPSS Statistics 24, whereby the chi-square test was obtained, obtaining a p = 0.235, which can be concluded that There is not an association between Diabetes mellitus 2 and multidrug-resistant pulmonary tuberculosis. An OR = 0.519, with 95% CI = [0.173-1.560] was obtained; thus determining that diabetes mellitus is not a risk factor for multidrug-resistant tuberculosis